2022
DOI: 10.1159/000526136
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Comparison of the Japanese Score and Other Scores in Patients with Nonvariceal Upper Gastrointestinal Bleeding: A Retrospective Study

Abstract: Background: Various scoring systems have been developed to predict endoscopic intervention, mortality, and rebleeding in patients with non-variceal upper gastrointestinal bleeding (NVUGIB); however, they have not been sufficiently validated in Korea. Therefore, this study aimed to evaluate the usefulness of several scoring systems in Korea by validating and comparing the Japanese score and other scores in Korean people with NVUGIB. Methods: The medical records of 1368 patients with NVUGIB were reviewed to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…[5] A previous study in South Korea demonstrated the superiority of the Japanese score in predicting the need for endoscopic intervention for patients with UGIB, except in patients with NVUGIB. [6] In this study, when the patient group was limited to those with PUB, the Japanese score showed superior predictive ability for the need for endoscopic intervention (AUC value: .724, P < .001) when compared with other scoring systems, including the GBS (AUC value: .587, P = .002). Compared with that observed in Choi study, the AUC value of the Japanese score for predicting the need for endoscopic intervention in patients with PUB was higher than that in patients with NVUGIB (AUC value: .699, P < .001).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…[5] A previous study in South Korea demonstrated the superiority of the Japanese score in predicting the need for endoscopic intervention for patients with UGIB, except in patients with NVUGIB. [6] In this study, when the patient group was limited to those with PUB, the Japanese score showed superior predictive ability for the need for endoscopic intervention (AUC value: .724, P < .001) when compared with other scoring systems, including the GBS (AUC value: .587, P = .002). Compared with that observed in Choi study, the AUC value of the Japanese score for predicting the need for endoscopic intervention in patients with PUB was higher than that in patients with NVUGIB (AUC value: .699, P < .001).…”
Section: Discussionmentioning
confidence: 62%
“…[ 5 ] A previous study in South Korea demonstrated the superiority of the Japanese score in predicting the need for endoscopic intervention for patients with UGIB, except in patients with NVUGIB. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If not managed promptly, it can be potentially life-threatening. Choi et al [2] demonstrated that although there exist a multitude of scoring systems to aid physicians in risk stratification for GI bleeding, it is important that these scoring systems are first validated in the local population. For patients presenting with overt or obscure GI bleeding, capsule endoscope is often used for investigation.…”
mentioning
confidence: 99%